Monitoração de propriedades mecânicas de polímeros com sensor à rede de Bragg - Lourenço Junior, Ivo de (2011)
This work shows results obtained with the use of fiber Bragg grating (FBG) transducer to monitor the drying process of latex paints. When a thin film of wet paint is dried on the substrate surface, the paint film change from a sticky liquid state to a solid state, transforming to a continuous, transparent and mechanically stable film. The mechanical deformations in this process were measured by the FBG sensor head, showing the real possibility of FBG strain sensor application in this area. To monitor the mechanical deformation in the film during the drying process, the FBG was packaged. The FBG packaging has two main functions: allows a better measurement of the paint mechanical deformation inherent to the drying process and also avoids paint poor adhesion to the bare optical fiber. The packaged FBG, showed that this is a promising device to be used for the measurement of stress evolution in paints during the drying time. The mechanical deformation during drying time of diluted latex paint also was investigated. Finally, a study about the mechanical deformation of a second coating application of latex paint was also carried out. The Bragg gratings used in this work were produced in photosensitive fibers by means of a phase-mask interferometric external fabrication technique at Núcleo de Dispositivos Fotônicos laboratories of UTFPR.